CASES RELATED TO THE RIGHTS AND LEGAL CAPACITY OF CITIZENS (SUBSTANTIVE AND PROCEDURAL LEGAL ASPECTS) - Normurotovna, Esanova Zamira (International Journal of Business, Law and Political Science, 2024)
The rights and legal capacity of citizens are fundamental components of the legal system, encompassing both substantive and procedural dimensions. The evolution of legal frameworks governing these rights reflects broader societal changes and varying judicial interpretations across jurisdictions. Despite extensive legal scholarship, there remains a critical gap in understanding how different legal systems address the interplay between substantive rights and procedural mechanisms, particularly in emerging and transitional contexts. This study aims to analyze and compare the substantive and procedural aspects of legal capacity and rights across diverse legal systems to identify commonalities, differences, and underlying principles. The analysis reveals significant variation in how legal systems define and enforce citizens' rights and capacities, influenced by historical, cultural, and legal factors. Specific procedural mechanisms, such as judicial review and administrative oversight, play pivotal roles in shaping substantive outcomes. This research provides a novel comparative perspective by integrating case studies from both developed and developing jurisdictions, offering new insights into the effectiveness and limitations of current legal frameworks. The findings have important implications for policymakers and legal practitioners, suggesting that reforms may be necessary to enhance consistency and fairness in the protection of citizens' rights and legal capacity, with potential benefits for both legal theory and practical application.